Analisis Spasial Permudaan Rotan Alam dan Keterkaitannya Dengan Kondisi Habitat Di Kesatuan Pengelolaan Hutan Lindung Unit X Provinsi Sulawesi Tengah - Akhbar, Rahmat Kurniadi; Asniati, Asniati (Universitas Tadulako)
The Unit X of Protection Forest Management Unit of Central Sulawesi Province with an area of 97,157.66 ha is one of the FMUs in Indonesia for the purpose of sustainable forest management. The FMU located in Poso District has a protected forest area of 68.17% and limited production forest of 31.83%. The objective of the study was to analyze spatial distribution and the number of natural rattan regeneration of the relationship with the habitat condition in protected forests of sub-mountain rain zones. Spatial analysis method used in the data of natural rattan inventory results in 2018 with the help of geographic information system technology. From the analysis result, it is known that the distribution of natural rattan regeneration of three types of rattan (tohiti, symbol and stem) is determined by land cover / vegetation factor, soil type, land system, geology, slope aspect with correlation value (r) 0.93 - 1 (strong positive correlation); other contributing factors are slope class and altitude with correlation value (r) 0.59 – 0.79 (medium positive correlation); while the precipitation is weakly correlated positively with the value (r) 0.16. Of the three types of rattan analyzed, rattan lambang have high adaptability compared to the other two types of rattan (rattan batang and rattan tohiti).Keywords: Natural rattan regeneration, sub-mountains rain zone, spatial analysis.